ON LINE TICKET SALES RESERVATION SYSTEM AT PO. SRIWIJAYA BENGKULU - Supperianto, Bambang; Hendrik, Billy; Arlis, Syafri (Jurnal TAM (Technology Acceptance Model), 2025)
The development of science and technology along with the times can support all activities carried out by humans. A computer is a set of electronic devices that are largely composed of hardware and software that work together in processing data provided or entered by the user. Computers have many features, namely being able to process data that are numbers, letters, images, sounds, symbols, and others. With computer technology, data processing will be easier and more efficient so that users do not need a long time to process data. PO. Sriwijaya Bengkulu is one of the service companies engaged in transportation. However, the processing of sales and purchase administration data at PO. Sriwijaya Bengkulu in booking tickets for this company is still using a manual system which makes it difficult for consumers to be able to order tickets so that consumers have to come to PO. Sriwijaya Bengkulu directly to do the ticket booking process. This research aims to create a new booking system that uses PHP software and MySQL database connected to internet technology at PO. Sriwijaya Bengkulu, so that booking tickets is easier and wider. The result of this research is an online sales system that is often called a reservation that can be accessed easily and efficiently.